Dietary patterns and the risk of CVD and all-cause mortality in older British men. Issue 7 (13th September 2016) - Atkins, Janice L.; Whincup, Peter H.; Morris, Richard W.; Lennon, Lucy T.; Papacosta, Olia; Wannamethee, S. Goya
Abstract: Dietary patterns are a major risk factor for cardiovascular morbidity and mortality; however, few studies have examined this relationship in older adults. We examined prospective associations between dietary patterns and the risk of CVD and all-cause mortality in 3226 older British men, aged 60–79 years and free from CVD at baseline, from the British Regional Heart Study. Baseline FFQ data were used to generate thirty-four food groups. Principal component analysis identified dietary patterns that were categorised into quartiles, with higher quartiles representing higher adherence to the dietary pattern. Cox proportional hazards examined associations between dietary patterns and risk of all-cause mortality and cardiovascular outcomes. We identified three interpretable dietary patterns: 'high fat/low fibre' (high in red meat, meat products, white bread, fried potato, eggs), 'prudent' (high in poultry, fish, fruits, vegetables, legumes, pasta, rice, wholemeal bread, eggs, olive oil) and 'high sugar' (high in biscuits, puddings, chocolates, sweets, sweet spreads, breakfast cereals). During 11 years of follow-up, 899 deaths, 316 CVD-related deaths, 569 CVD events and 301 CHD events occurred. The 'high-fat/low-fibre' dietary pattern was associated with an increased risk of all-cause mortality only, after adjustment for confounders (highest v. lowest quartile; hazard ratio 1·44; 95 % CI 1·13, 1·84). Adherence to a 'high-sugar' diet was associated with a borderline significant trend for an increased risk of CVD and CHD events. The 'prudent' diet did not show a significant trend with cardiovascular outcomes or mortality. Avoiding 'high-fat/low-fibre' and 'high-sugar' dietary components may reduce the risk of cardiovascular events and all-cause mortality in older adults.